63.6k views
0 votes
The polynomial x^2+3x-1 is a factor of x^4+3x^3-2x^2-3x+1 true or false?

1 Answer

6 votes

Answer:

Yes, it is true that
x^2+3x-1 is a factor of
x^4+3x^3-2x^2-3x+1.

Explanation:

Let us try to factorize
x^4+3x^3-2x^2-3x+1


x^4+3x^3-2x^2-3x+1\\\Rightarrow x^4-2x^2+1-3x+3x^3

Let us try to make a whole square of the given terms:


\Rightarrow (x^2)^2-2* x^2 * 1+1^2+3x^3-3x\\\Rightarrow (x^2-1)^2+3x^3-3x\\

--------------

Formula used above:


a^(2) -2 * a * b +b^(2) = (a-b)^2

In the above equation, we had
a = x, b = 1.

--------------

Further solving the above equation, taking
3x common out of
3x^3-3x


\Rightarrow (x^2-1)^2+3x(x^2-1)\\

Taking
(x^(2) -1) common out of the above term:


\Rightarrow (x^2-1)((x^2-1)+3x)\\\Rightarrow (x^2-1)(x^2+3x-1)

So, the two factors are
(x^2-1)\ and\ (x^2+3x-1).


\therefore The statement that
x^2+3x-1 is a factor of
x^4+3x^3-2x^2-3x+1 is True.

User Steven Carlson
by
5.9k points